EVALUATION OF ROAD AND INTERSECTION RESEARCH PERFORMANCE USING BIBLIOMETRIC METHODS: LITERATURE STUDY SCOPUS BASED - Maula, Zaid; Paikun, Paikun (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2025)
This study aims to evaluate research trends related to road performance and intersection through a bibliometric approach. By utilizing the Scopus database, analysis was conducted on scientific publications containing the keywords “evaluation AND road performance OR intersection” within a certain period of time. The bibliometric method used includes analysis of publications based on the number of documents, country of origin, institutional affiliation, as well as visualization of author collaboration networks and frequently occurring keywords. The results show that this topic has received widespread attention globally, with an increase in the number of publications in recent years. The United States, China, and India are the countries with the largest contribution of publications, while institutions such as Tongji University and University of California are the most active affiliates. Keywords such as “intersection”, “traffic performance”, and “evaluation” dominate in the co-occurrence network, reflecting the research focus on traffic performance evaluation at conflict points such as intersections. This research provides a comprehensive overview of the direction and potential development of studies in the field of road and intersection performance, and provides a basis for future researchers to determine the focus and direction of research.